Remarks at the African Union Summit, Addis Ababa - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, addressed the challenges and opportunities for World Bank Group cooperation with the African Union. He discussed the following topics: (i) Millennium Development Goals have become critical for social development in Africa; (ii) growth and opportunity for Sub-Saharan Africa; (iii) natural resource development; (iv) post-conflict countries and those in fragile situations; and (v) the danger of high energy and food prices.